Effect of different crystalline directions on the mechanical properties and processing maps of Zr-Nb alloy for orthopedic applications - Ali Rajaee; Mohsen Asadi Asadabad; Behrooz Shayegh Boroujeny (Heliyon)
In the current study, the effect of direction on the hot compression behavior, processing map, and microstructure of Zr-Nb alloy after bidirectional hot forging was studied. Accordingly, the alloy billet was hot-forged and samples at different directions were extracted. Phase changes and microstructure of the samples were characterized. Additionally, hot compression tests were carried out on the samples in the temperature and strain rate ranges of 800–900 °C and 0.001–1 s−1, respectively. Microstructure examinations revealed that the forging resulted in the formation of various alpha spherical grains elongated along the forging direction. Along the directions of 30 and 60°, the high strain rate during forging caused the formation of secondary recrystallized grains in addition to grains elongated in the forging direction. Hardness measurement results showed that the highest hardness was related to the zero-degree direction due to the high fraction, refinement, and morphology of the alpha phase formed during the hot forging process. Full recrystallization of hot-compression samples was evident at 850 °C. Processing maps suggested the optimum deformation of the alloy to be within the strain rates 0.01–0.001 at 850 °C. Consequently, deformation within this range results in the desired dynamic recrystallization phenomenon.